Cardiac Tissue Engineering for Translational Cardiology: From In Vitro Models to Regenerative Therapies - Abdullah Jabri; Bader Taftafa; Abdulaziz Mhannayeh; Mohamed Alsharif; Tasnim Abbad; Sana Ahmed; Eman A. Alshehri; Abdulrahman Elsalti; Jibran Khan; Tanveer Ahmad Mir; Ahmed Yaqinuddin (Bioengineering)
Cardiovascular diseases (CVD) are the primary cause of death and disability around the world. Over the past decades, several conventional model systems based on two-dimensional (3D) monolayer cultures or experimental animals have been adopted to dissect and understand heart diseases in order to develop treatment modalities. However, traditional models exhibit several limitations in recapitulating human-specific key physiological and pathological characteristics, which highlights the necessity of developing physiologically relevant models. In recent years, tissue engineering approaches have been extensively employed to generate revolutionary three-dimensional (3D) cardiac models. In particular, the combined use of various bioengineering strategies and cellular reprogramming approaches has facilitated the development of various models. This review presents an overview of different approaches (bioprinting, scaffolding, and electrospinning) for creating bioengineered cardiac tissue models. Next, a broad survey of recent research related to the modeling of various cardiac diseases is presented. Finally, current challenges and future directions are proposed to foster further developments in the field of cardiac tissue engineering.